Civil liability in the excavation of minerals c - Massura Putri Syahru; Yulia Y; Marlia Sastro (Fakultas Hukum Universitas Malikussaleh, 2019)
The case of excavation of excavated land C which occurred in Muara Satu Subdistrict, Lhokseumawe City, excavation activities of C excavated soil in the Padang Sakti Mountains and Paloh Punti Muara Satu Lhokseumawe areas without a permit, became increasingly uncontrollable by the excavation owner and the excavation entrepreneur. Dredging activities in the area are of great concern to a number of people because they can cause environmental damage.The purpose of this study is to identify and explain civil liability in extracting C minerals, civil liability barriers in extracting C minerals, and efforts to resolve civil liability barriers in extracting C minerals in Lhokseumawe City. This type of research is an empirical juridical research, namely an integrative and conceptual method of analysis to identify, process and analyze documents to understand the meaning, significance, and relevance that produces descriptive data in the form of written or spoken words from people or observed behavior. The results showed that the form of Civil Accountability in extracting C minerals in Muara Satu Subdistrict, Lhokseumawe City, such as the responsibility of the perpetrator to the victim of excavating C excavation material due to illegal actions, pollution and / or environmental destruction, loss of other people or the environment, and accountability. activities to pay compensation and / or take certain actions. Obstacles to civil accountability in excavating C excavation materials in Muara Satu Kota Lhokseumawe include internal barriers including lack of knowledge of legal responsibility, lack of concern for environmental damage, and lack of coordination between the authorities. Then external factors due to economic limitations, factors of limited education, lack of legal awareness in the community and lack of coordination between parties. Efforts to resolve internal Civil Accountability Barriers include negotiating with the community, improving coordination with all related parties, and conducting mediation. Then efforts to resolve external obstacles include coordination with all related parties, regularly supervising mining activities without permits, coordinating between parties and Deliberations and conducting community legal outreach. It is recommended that law enforcement against the excavation of illegal land C excavation should be maximized and it is necessary to arrest the perpetrators of illegal land extraction and not only take preventive measures.